Agricultural wealth better predicts mental wellbeing than market wealth among highly vulnerable households in Haiti: Evidence for the benefits of a multidimensional approach to poverty. Issue 2 (12th September 2019) - Lachaud, James; Hruschka, Daniel J.; Kaiser, Bonnie N.; Brewis, Alexandra
Abstract: Objectives: Lack of wealth (poverty) impacts almost every aspect of human biology. Accordingly, many studies include its assessment. In almost all cases, approaches to assessing poverty are based on lack of success within cash economies (eg, lack of income, employment). However, this operationalization deflects attention from alternative forms of poverty that may have the most substantial influence on human wellbeing. We test how a multidimensional measure of poverty that considers agricultural assets expands the explanatory power of the construct of household poverty by associating it with one key aspect of wellbeing: symptoms of mental health. Methods: We used the case of three highly vulnerable but distinctive communities in Haiti—urban, town with a rural hinterland, and rural. Based on survey responses from adults in 4055 geographically sampled households, linear regression models were used to predict depression and anxiety symptom levels controlling for a wide range of covariates related to detailed measures of material poverty, including cash‐economy and agricultural assets, income, financial stress, and food insecurity. Results: Household assets related to the cash economy were significantly associated with lower (ie, better) depression scores (−0.7, [95% CI: −1.2 to, −0.1]) but unrelated to anxiety scores (−0.3 [95% CI: −0.8 to 0.3]). Agricultural wealth was significantly—and more strongly—associated with both reductions in depression symptoms (−1.4 [95% CI: −2.2 to −0.7]) and anxiety symptoms (−1.8 [95% CI: −2.6 to −1.0]). These associations were consistent across the three sites, except in the fully urban site in Port‐au‐Prince where level of depression symptoms was not significantly associated with household agricultural wealth. Conclusions: Standard measures of poverty based on success in the cash economy can mask important associations between poverty and wellbeing, in this case related to household‐level subsistence capacity and crucial food‐producing household assets.